GENETIC VARIABILITY, CORRELATION AND PATH ANALYSIS FOR YIELD ATTRIBUTES IN PIGEONPEA - S. K. SAROJ; M. N. SINGH; KUMAR, RAVINDRA; SINGH, TEJVEER; MK SINGH (The Bioscan, 2013)
The phenotypic and genotypic variances, correlation and path coefficient, heritability and genetic advances were estimated for grain yield and yield traits in 70 pigeonpea genotypes. The highest GCV was recorded for number of secondary branches/plant (61.81) followed by pods/plant (38.34). Heritability in broad sense ranged from 61.33 (seeds/pod) to 98.26 (days to 50% flowering). High genetic advance were observed for number of primary branches/plant (60.61), number of secondary branches/plant (154.10), 100-seed weight (50.82), grain yield/plant (84.65), pods/plant (92.59), plant height (33.83) and days to 50% flowering (45.05) indicating the prevalence of additive gene action for inheritance of these traits. Correlation and Path coefficient analysis (genotypic and phenotypic) revealed that pods/plant (0.858**), 100-seed weight (0.370**), days to 50% flowering (0.458**), primary branches (0.357**) and secondary branches (0.302**) had maximum direct effect resulted significantly positive correlation with grain yield/plant. These traits can be used to improve the grain yield of pigeonpea.